Archetypal figures in "the Snows of Kilimanjaro" : Hemingway on flight and hospitality - Anderson, David L. (David Louis) (The Kent State University Press, 2019)
"Anderson explores the richness of Hemingway's short story "The Snows of Kilimanjaro," widely considered Hemingway's greatest, and introduces a new critical term, "Man on Trail," borrowed from Jack London. The man on trail is being pursued, ultimately by death, is in need of hospitality, a friend. The concept is older than London, is as old as the species. Anderson takes the reader to Jung, Campbell, to archetypal criticism, and schools the reader on its manifestations, from ancient literature to Bob Dylan, eventually taking us to Hemingway's fiction. He demonstrates that the man-on-trail plot was an instinctive structure for Hemingway"--